Effect of intermittent pneumatic compression on preventing deep vein thrombosis using microfluidic vein chip - Dai, Hongtao; Chai, Senlin; Yao, Yao; Tang, Wenlai; Shi, Jianping; Jiang, Qing; Zhu, Liya (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Deep Vein Thrombosis (DVT) is a common disease, frequently afflicting the lower limb veins of bedridden patients. Intermittent Pneumatic Compression (IPC) is often employed as an effective solution for this problem. In our study, a random selection of 264 patients underwent IPC treatment for either one or eight hours daily. The rate of severe venous thrombosis was substantially reduced in the IPC-treated group compared to the control group. However, real-time monitoring of blood flow during IPC operation periods remains a challenge. Methods: Here, microfluidic chip methodology is used to create an in vitro vein-mimicking platform integrating venous valves in a deformable channel. Whole blood of patients after knee surgery was perfused into the venous channel at a controlled flow rate obtained from patients with IPC treatment clinically. Results: According to the numerical simulations results, both of an increase in compressive pressure and a decrease in time interval of IPC device can accelarete blood flow rate and the shear stress within the vein. The vein chip experiments also reveal that the fibrin accumulation can be greatly lowered in IPC treated group, indicating less thrombosis formation in future. A time interval of 24 seconds and a maximum contraction pressure of 40 mmHg were proved to be the most effective parameters for the IPC device used in our clinical trail. Conclusion: This vein chip presents a novel method for observing the functional mechanisms of IPC device for DVT prevention. It provides crucial data for further standardization and optimization of IPC devices in clinical usage.